Late Diagnosed Left Coronary to the Pulmonary Artery Large Fistulae: An Interesting and Incidental Cath Lab Finding - Marcos Danillo P. Oliveira; Pedro H. M. Craveiro de Melo; Érlon O. Abreu-Silva; Fernando Barbiero Coura; Gleyson Moraes Rios; Daniel Izzet Potério (Case Reports in Cardiology)
Coronary artery anomalies are congenital changes in their origin, course, and/or structure. Most of them are discovered as incidental findings during coronary angiographic studies or at autopsies. A coronary artery fistulae involve a communication between a coronary artery and a chamber of the heart or any segment of the systemic or pulmonary circulation. We present herein the case of a 67-year-old man with a recent history of exertional angina and dyspnea to usual daily activities whose coronary angiogram revealed an interesting and incidental coronary-pulmonary artery large fistulae.